(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the current status of anxiety disorders in patients with heart failure treated as inpatients at the Vietnam National Heart Institute. Subjects and methods: Cross-sectional study of 125 patients diagnosed with heart failure treated as inpatients at the Vietnam Heart Institute from July 2024 to May 2025. Results: Of the total 125 patients participating in the study, the proportion of men accounted for 53.4%, the average age of the study subjects was 64.59 ± 14.93; 51.2% of the patients had anxiety disorders. The group of symptoms of autonomic nervous system stimulation and chest and abdominal symptoms appeared in 100% of patients with anxiety disorders. The most common symptom was palpitations and tachycardia, occurring in 100% of patients. Other symptoms such as shortness of breath (98.4%), sweating (95.3%), chest pain and difficulty sleeping due to anxiety (92.2%), and dry mouth (87.5%) were also common. Conclusion: The rate of anxiety disorders in patients with heart failure is quite high (51.2%) and should be noted in this group of patients.